Core–Shell Structures Prepared by Atomic Layer Deposition on GaAs Nanowires - Ursaki, Veaceslav V.; Lehmann, Sebastian; Zalamai, Victor V.; Morari, Vadim; Nielsch, Kornelius; Tiginyanu, Ion M.; Monaico, Eduard V. (Crystals, 2022)
GaAs nanowire arrays have been prepared by anodization of GaAs substrates. The nanowires produced on (111)B GaAs substrates were found to be oriented predominantly perpendicular to the substrate surface. The prepared nanowire arrays have been coated with thin ZnO or TiO2 layers by means of thermal atomic layer deposition (ALD), thus coaxial core–shell hybrid structures are being fabricated. The hybrid structures have been characterized by scanning electron microscopy (SEM) for the morphology investigations, by Energy Dispersive X-ray (EDX) and X-ray diffraction (XRD) analysis for the composition and crystal structure assessment, and by photoluminescence (PL) spectroscopy for obtaining an insight on emission polarization related to different recombination channels in the prepared core–shell structures.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anodization; atomic layer deposition; coaxial core–shell structures; emission polarization; nanowires; photoluminescence spectroscopy